2022
DOI: 10.1016/j.landusepol.2021.105833
|View full text |Cite
|
Sign up to set email alerts
|

What is the future of abandoned agricultural lands? A systematic review of alternative trajectories in Europe

Abstract: Agricultural land abandonment and its impacts on landscape features have been a striking characteristic of many European rural areas over the last decades. Although previous research identified drivers and environmental impacts of abandonment, few described the post-agricultural abandonment trajectories. However, examining the driving forces leading to different post-agricultural abandonment trajectories is key to understand how alternative uses of these lands can be developed to address the environmental, eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 78 publications
(114 reference statements)
1
47
0
Order By: Relevance
“…However, there is some indication that abandonment may be more durable in Europe, another region that has experienced significant abandonment ( 11 , 35 ). A recent review of post-abandonment trajectories in Europe found that in most cases (64.44%, or 87 of 135 studies reviewed), abandoned lands went through secondary succession and transitioned toward seminatural landscapes, although Eastern Europe and Russian abandonment may be more prone to recultivation ( 63 ). This study did not include time since initial abandonment as a factor, however, and the differences in abandonment persistence between regions merit future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some indication that abandonment may be more durable in Europe, another region that has experienced significant abandonment ( 11 , 35 ). A recent review of post-abandonment trajectories in Europe found that in most cases (64.44%, or 87 of 135 studies reviewed), abandoned lands went through secondary succession and transitioned toward seminatural landscapes, although Eastern Europe and Russian abandonment may be more prone to recultivation ( 63 ). This study did not include time since initial abandonment as a factor, however, and the differences in abandonment persistence between regions merit future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Abandoned agricultural land has often been discussed as providing capacity for afforestation in order to respond to environmental policy goals [26]. Therefore, we aim to explore the potentially required land area for planting three billion trees on abandoned agricultural areas.…”
Section: Abandoned Agricultural Landmentioning
confidence: 99%
“…Afforestation of agricultural land and changing degraded land to forests seems a relatively cost-effective climate change mitigation option (Fuss et al 2018) and is among the major mitigation measures included in Nationally Determined Contributions (NDCs) submitted by countries to the UNFCCC. While the afforestation of degraded land can deliver substantial mitigation benefits with co-benefits to biodiversity (Lewis et al 2019;Fayet et al 2022), the afforestation of cropland may compromise food production (Fuss et al 2018). As a final note regarding afforestation, when employed on native grasslands, it has a significant negative effect on biodiversity as many species require rich, open habitats (Burrascano et al 2016).…”
Section: Synergies Between Climate Change Mitigation and Biodiversitymentioning
confidence: 99%